Membangun Sinergisitas antara Sains dan Nilai-Nilai Agama (Inovasi Pembelajaran dalam Pendidikan Islam dalam Perpektif Ontologis, Epistimologis, dan Aksiologis) - Abd. Warits (STID Raudlatul Iman Sumenep, 2024)
This article examines efforts to build synergy between science, religious values, and learning innovation in Islamic education through ontological, epistemological, and axiological approaches. This study departs from the reality that the separation between science and religion often creates a dichotomy that hinders the development of holistic science and transformative education. Ontologically, this article highlights the harmony of the nature of science and religion as a means of understanding truth that comes from God. In the epistemological realm, synergy can be achieved by formulating an integrative scientific paradigm that recognizes revelation as a source of knowledge that complements reason and empirical experience. Axiologically, this collaboration produces knowledge that is not only technical, but also meaningful, provides real benefits for the benefit of humanity, and encourages the renewal of learning methods based on spiritual values. This research uses a qualitative approach with in-depth literature analysis, including classical and modern Islamic texts, philosophical theories of science, and contemporary learning innovation models. The results of the study show that the integration of science, religion and learning innovation can be the foundation for developing Islamic education that is more contextual, adaptive and relevant, especially in responding to the challenges of the times. This article contributes to strengthening the Islamic education paradigm which not only integrates spiritual and scientific values, but also presents creative learning approaches to form complete humans. The synergy of science, religion and learning innovation is a strategic step in realizing a civilization that is just, sustainable and oriented towards the benefit of the people. Artikel ini mengkaji upaya membangun sinergisitas antara sains, nilai-nilai agama, dan inovasi pembelajaran dalam pendidikan Islam melalui pendekatan ontologis, epistemologis, dan aksiologis. Kajian ini berangkat dari realitas bahwa pemisahan antara sains dan agama sering kali menciptakan dikotomi yang menghambat pengembangan ilmu pengetahuan yang holistik dan pendidikan yang transformatif. Secara ontologis, artikel ini menyoroti keselarasan hakikat sains dan agama sebagai sarana untuk memahami kebenaran yang bersumber dari Tuhan. Dalam ranah epistemologis, sinergisitas dapat dicapai dengan merumuskan paradigma keilmuan integratif yang mengakui wahyu sebagai sumber pengetahuan yang melengkapi akal dan pengalaman empiris. Aksiologis, kolaborasi ini menghasilkan ilmu yang tidak hanya bersifat teknis, tetapi juga bermakna, memberikan manfaat nyata bagi kemaslahatan umat manusia, dan mendorong pembaruan metode pembelajaran berbasis nilai spiritual. Penelitian ini menggunakan pendekatan kualitatif dengan analisis literatur yang mendalam, mencakup teks-teks keislaman klasik dan modern, teori filsafat ilmu, serta model inovasi pembelajaran kontemporer. Hasil kajian menunjukkan bahwa integrasi sains, agama, dan inovasi pembelajaran dapat menjadi fondasi pengembangan pendidikan Islam yang lebih kontekstual, adaptif, dan relevan, terutama dalam menjawab tantangan zaman. Artikel ini berkontribusi pada penguatan paradigma pendidikan Islam yang tidak hanya mengintegrasikan nilai-nilai spiritual dan keilmuan, tetapi juga menghadirkan pendekatan pembelajaran kreatif untuk membentuk manusia paripurna. Sinergisitas sains, agama, dan inovasi pembelajaran menjadi langkah strategis dalam mewujudkan peradaban yang berkeadilan, berkelanjutan, dan berorientasi pada kemaslahatan umat.